Phase-shifted PWM strategy of a seven-level single-phase current source inverter for grid-connection systems - Napaphat Lekgamheng (2018)
This paper presents a detailed analysis of a seven-level single-phase current source inverter for grid-connection systems. The aim of this research was to control high power factor operation, injecting a sinusoidal current flowing into the utility grid. The proposed two-stage power conversion strategies consisted of a dc-dc multilevel converter and a current source inverter, which operated with high switching and line frequency. A proposed topology is used to produce a seven-level current output with a phase-shifted PWM technique. A simple method is presented to improve the total harmonic distortion and power factor requirement. The feasibility of the proposed method was verified by simulation and experimental results. © 2013 IEEE.